Characterization, expression, enzymatic activity, and functional identification of cathepsin S from black rockfish Sebastes schlegelii. Issue 93 (October 2019) - Wang, Guang-hua; He, Shu-wen; Du, Xue; Xie, Bing; Gu, Qin-qin; Zhang, Min; Hu, Yong-hua
Abstract: Cathepsin S belong to the cathepsin L-like family of cysteine cathepsins. It is well known that Cathepsin S participate in various physiological processes and host immune defense in mammals. However, in teleost fish, the function of cathepsin S is less investigated. In the present study, a cathepsin S homologue (SsCTSS) from the teleost fish black rockfish ( Sebastes schlegelii ) were identified and examined at expression and functional levels. In silico analysis showed that three domains, including signal peptide, cathepsin propeptide inhibitor I29 domain, and functional domain Pept_C1, were existed in the cathepsin. SsCTSS possesses a peptidase domain with three catalytically essential residues (Cys25, His162, and Asn183). Phylogenetic profiling indicated that SsCTSS are evolutionally close to the cathepsin S of other teleost fish. The expression of SsCTSS in immune-related tissues was upregulated in a time-dependent manner upon bacterial pathogen infection. Purified recombinant SsCTSS (rSsCTSS) exhibited apparent peptidase activity, which was remarkably declined in the presence of the cathepsin inhibitor E−64. rSsCTSS showed strong binding ability to LPS and PGN, the major constituents of the outer membranes of Gram-negative and Gram-positive bacteria, respectively. rSsCTSS also exhibited the capability of agglutination to different bacteria. The knockdown of SsCTSS attenuated the ability of host to eliminate pathogenic bacteria. Taken together, our results suggested that SsCTSS functions as cysteine protease which might be involved in the antibacterial immunity of black rockfish. Highlights: Expression of SsCTSS was upregulated during bacterial infection. rSsCTSS exhibited apparent peptidase activity. rSsCTSS exhibited apparent binding activities against LPS, PGN and different bacteria. The knockdown of SsCTSS attenuated the ability of host to eliminate pathogenic bacteria.